Current issues in generative Hebrew linguistics - Armon-Lotem, Sharon; Danon, Gabi; Rothstein, Susan, 1958- (Linguistik aktuell, 2008)
This volume presents a collection of specially commissioned papers devoted to analyzing the linguistics of Modern Hebrew from a number of perspectives. Various aspects of Modern Hebrew grammar are discussed including the structure of the lexicon, grammati.